MACHINE TRANSLATION VS. HUMAN TRANSLATION: A COMPARATIVE STUDY OF ACCURACY AND CONTEXT - Jovliyeva Nafosat Bahodir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article examines the differences between machine translation (MT) and human translation (HT) in terms of accuracy, contextual understanding, and linguistic quality. As artificial intelligence and neural machine translation systems continue to advance, questions arise regarding their reliability and ability to replace human translators. The study explores how both approaches handle linguistic nuances, idiomatic expressions, cultural references, and contextual meaning. Through comparative analysis, the paper highlights that while machine translation offers speed and convenience, it still struggles with cultural and pragmatic accuracy that human translators naturally maintain. The findings suggest that the future of translation lies in the collaboration between humans and machines rather than complete replacement.